2004
DOI: 10.4049/jimmunol.172.12.7726
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine-Activated Mast Cells Induce IgE Synthesis by B Lymphocytes: An A2B-Mediated Process Involving Th2 Cytokines IL-4 and IL-13 with Implications for Asthma

Abstract: Adenosine provokes bronchoconstriction in asthmatics through acute activation of mast cells, but its potential role in chronic inflammation has not been adequately characterized. We hypothesized that adenosine up-regulates Th2 cytokines in mast cells, thus promoting IgE synthesis by B lymphocytes. We tested this hypothesis in human mast cells (HMC-1) expressing A2A, A2B, and A3 adenosine receptors. The adenosine analog 5′-N-ethylcarboxamidoadenosine (NECA) (10 μM) increased mRNA expression of IL-1β, IL-3, IL-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
132
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 69 publications
5
132
0
Order By: Relevance
“…Although HMC-1 cells express very low levels of functional FcRI (28), this human mast cell line has proven useful to uncover the A 2B receptor-dependent up-regulation of Th2 cytokines and angiogenic factors (11,14), a process independent from FcRI stimulation as we show in the current study in BMMCs. Because the use of an established cell line for detailed analysis of intracellular signaling pathways could be advantageous due to availability of plentiful material and better reproducibility of results, we next sought to determine whether HMC-1 can serve as an appropriate model to study A 2B receptor-dependent regulation of mast cell cytokine and growth factor production, by comparing IL-13 and VEGF regulation in BMMCs and HMC-1 cells.…”
Section: Hmc-1 As a Model To Study A 2b Receptor-dependent Regulationmentioning
confidence: 57%
See 1 more Smart Citation
“…Although HMC-1 cells express very low levels of functional FcRI (28), this human mast cell line has proven useful to uncover the A 2B receptor-dependent up-regulation of Th2 cytokines and angiogenic factors (11,14), a process independent from FcRI stimulation as we show in the current study in BMMCs. Because the use of an established cell line for detailed analysis of intracellular signaling pathways could be advantageous due to availability of plentiful material and better reproducibility of results, we next sought to determine whether HMC-1 can serve as an appropriate model to study A 2B receptor-dependent regulation of mast cell cytokine and growth factor production, by comparing IL-13 and VEGF regulation in BMMCs and HMC-1 cells.…”
Section: Hmc-1 As a Model To Study A 2b Receptor-dependent Regulationmentioning
confidence: 57%
“…We have previously demonstrated that stimulation of A 2B receptors in human mast cell line HMC-1 increases production of proinflammatory Th2 cytokines IL-4 and IL-13 (11,12), as well as angiogenic factors IL-8 and vascular endothelial growth factor (VEGF) (13,14). Furthermore, conditioned medium from these activated mast cells promoted capillary formation in an angiogenesis model (14) and induced IgE synthesis in naive B lymphocytes (11). For this and other reasons, mast cell A 2B adenosine receptors have been suggested to promote pulmonary inflammation and airway remodeling associated with asthma.…”
mentioning
confidence: 99%
“…In mouse mast cells, A 3 AR activation has been shown to induce mast-cell degranulation 171 . It has been suggested that this effect is mediated by the A 2B AR in human and canine mast cells [172][173][174] . A bioavailable thiazole derivative that acts as a mixed antagonist at A 2B and A 3 ARs has been proposed to be a candidate therapeutic agent for the treatment of asthma 175 ; however, this has not been tested in animal models.…”
Section: Ars As Targets In Pulmonary Disordersmentioning
confidence: 99%
“…The mechanisms by which adenosine is regulating the levels of IL-13 and IL-4 are not known but may relate to the regulation of intracellular cAMP levels. Increased IL-4 and IL-13 production is associated with elevations in cAMP (41)(42)(43), and recent findings have demonstrated that adenosine can promote the expression of IL-4 and IL-13 in mast cells by engaging the A 2B AR (44), which couples to G αs to activate adenylate cyclase and elevate cAMP (15). The A 2B AR has relatively low affinity for adenosine.…”
Section: Figurementioning
confidence: 99%